Fostering Entrepreneurial Interest: Role Models, Entrepreneurship Education, And Locus Of Control In Banyuwangi Vocational High School Students - Moh. Nasir Jazuli; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (International Education Trend Issue, 2023)
High unemployment rates and limited job opportunities globally intensify competition among applicants. In Indonesia, particularly at the vocational school level, unemployment is a growing concern, with graduates constituting a significant portion of job seekers. The main challenges lie in the quality of entrepreneurship education and the lack of interest in entrepreneurship among vocational school students, leading to a mismatch between graduates and market needs. This research addresses the knowledge gap by focusing on entrepreneurship education, teacher role models, and the impact of locus of control on vocational school students' interest in entrepreneurship. The study, conducted in three vocational schools in Banyuwangi, aims to understand the complex interactions between these factors and their influence on entrepreneurial interest. Using quantitative methods, the research involves 214 vocational school students who have taken entrepreneurship or craft subjects, focusing on marketing majors. The data analysis utilizes SmartPLS 3.3.3 and Structural Equation Model (SEM) to examine the relationships. Findings reveal a positive correlation between entrepreneurship education and students' entrepreneurial intentions and locus of control. Similarly, family role models positively impact students' entrepreneurial intentions and locus of control. A higher locus of control is associated with increased entrepreneurial intentions. Moreover, both entrepreneurship education and family role models contribute to heightened entrepreneurial intentions through locus of control. The implications suggest that enhancing entrepreneurship education and promoting family role models can effectively strengthen vocational school students' interest in entrepreneurship. Locus of control plays a crucial mediating role in this process. The research outcomes offer valuable insights for educators and policymakers to improve the effectiveness of entrepreneurship education, emphasizing the role of teachers as role models and fostering an understanding of locus of control. This approach aims to positively impact unemployment rates and local economic growth